The Role of the Concept of Agape in Improving Aristotle’s Ethics - Rakhmawati, Silvia Maudy (Fakultas Filsafat, Universitas Gadjah Mada Yogyakarta, 2024)
This research attempted to solve a fundamental philosophical problem in Aristotle's ethics, which was considered insufficient to provide an explanation of what principles must be obeyed by agents of virtue to determine morally right actions. Therefore, this research was conducted to analyze the role of the concept agape in improving Aristotle’s ethics, and its relevance to well-being. This research method was literature-based qualitative research. The research type applied was descriptive of the expert’s thoughts. The agape concept in this study was independent of metaphysical and theological orientations. The concept of agape in this discussion did not refer to God but was directed to the realm of virtue. The high moral value on which agape is based is rationality. Morally right action is an action that emanates from virtue, which is shaped by the purpose of love and wisely carried out in a relational context using practical reason involving situational and consequence considerations. The essential role of agape in virtue is as a constituent of well-being. What one brings to life becomes one’s own life, in line with Aristotle's classical notion that virtue contributes to eudaimonia.